Kafe sebagai Ruang Belajar Alternatif: Studi Deskriptif tentang Budaya Nongkrong Mahasiswa di Surabaya - Damanik, Netanya Evelyn Berliana (L-SAPIKA INDONESIA, 2025)
The growing frequency of students visiting cafés as study spaces reflects a cultural transformation in the use of urban public spaces. Cafés are no longer merely places for leisure, but have evolved into important non-formal learning environments for university students. This study aims to explore how students perceive the culture of hanging out in cafés, what factors influence their preferences, and how gender and socioeconomic background shape their engagement with such spaces. A descriptive quantitative method was employed, involving a survey of 75 active students in Surabaya who regularly spend time studying in cafés. The findings show that the majority of respondents use cafés to complete academic tasks and engage in group discussions, with an average frequency of twice a week and a duration of approximately four hours per visit. Gender differences were found in space usage preferences, and students from lower-income backgrounds face barriers in accessing cafés as study spaces. These findings suggest that cafés have become embedded in the cultural identity of urban student learning, while also raising concerns about spatial justice and inclusivity in higher education learning environments.